2008
DOI: 10.1002/dev.20287
|View full text |Cite
|
Sign up to set email alerts
|

Enriched environment restores impaired hippocampal long‐term potentiation and water maze performance induced by developmental lead exposure in rats

Abstract: Lead (Pb2+) exposure in children can induce long lasting deficits in cognitive function and has been modeled in experimental animals. Based on previous studies which demonstrated that learning impairments resulting from developmental Pb2+ exposure were reversible if the animals were provided with an enriched environment, here, we asked if environmental enrichment (EE) could also reverse long-term potential (LTP) impairment induced by lead. Rats drank 1,500 ppm lead acetate (PbAc) solution or distilled water th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 28 publications
1
25
0
1
Order By: Relevance
“…In each experiment, an enriched environment reversed Pb 2 + -induced long-term potentiation impairment or spatial learning deficits. 9,32 The low correlation coefficients (Table 3) suggest that additional confounding factors were responsible for causing the observed variation in our data. First, individual position within the social hierarchy was not tracked.…”
Section: Social Behavior In Lead-exposed Zebrafishmentioning
confidence: 53%
See 1 more Smart Citation
“…In each experiment, an enriched environment reversed Pb 2 + -induced long-term potentiation impairment or spatial learning deficits. 9,32 The low correlation coefficients (Table 3) suggest that additional confounding factors were responsible for causing the observed variation in our data. First, individual position within the social hierarchy was not tracked.…”
Section: Social Behavior In Lead-exposed Zebrafishmentioning
confidence: 53%
“…A further complication, and one that is investigated in the studies described in this article, is the experimental apparatus used to elicit specific behavioral outcomes. It has been observed that environmental enrichment can mitigate the learning deficits caused by developmental Pb 2 + exposure, 32 suggesting that the design of the testing chamber or protocol may affect behavioral outcomes. From this perspective, mirrors have been used as means to stimulate social interactions in many vertebrate species, including fishes.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable evidences had shown that EE treatment was beneficial for cognitive functions both in normal and pathological conditions (Cao et al 2008;Anastasia et al 2009;Hirata et al 2011;Simao et al 2012;Beauquis et al 2013;Doulames et al 2014;Piazza et al 2014). However, few studies addressed whether and how EE Xiaoqian Zhang and Tingting Liu contributed equally to this work.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, local efforts will be taken to counteract the negative consequences of exposure to lead for Flint’s children. Several recent publications support the positive effects that enriched home environments can have on cognition and behavior in both human and animal studies [74,75,76]. …”
Section: Future Directions: How To Move Toward Environmental Justicementioning
confidence: 90%